Behavioral hotspots of bottlenose dolphins in industrialized ship channels - Mills, Eliza M. M.; Piwetz, Sarah; Orbach, Dara N. (Frontiers in Marine Science, 2024)
Anthropogenic activity in coastal areas can damage marine habitats and alter marine mammal behavior and habitat use. Understanding behavioral associations with diverse habitat features in industrialized coastal areas is crucial for marine mammal conservation management. A shore-based digital theodolite was used to assess the behavioral states and habitat use of common bottlenose dolphins (Tursiops truncatus) off Port Aransas, Texas across seasons. The relationship between behavioral states and environmental and geographical variables were analyzed. Behavioral hotspots were identified. Dolphins frequently foraged (46%), indicating the area is an important feeding ground. Dolphins also traveled (25%) and milled (22%), with less frequent occurrences of socializing (6%) and resting (1% of observations). Season, time of day, and distance to shoreline were significant predictors of foraging and traveling behavioral states. Dolphins engaged in all behavioral states closer to seawall shorelines than to mangroves and natural seagrass beds, suggesting that hard shoreline features may influence daily activity patterns. Despite daily anthropogenic operations, bottlenose dolphins use features of the industrialized area (i.e., deeply dredged channels, human-engineered seawalls) to engage in a variety of behaviors. Monitoring of dolphin behavioral states and habitat use in active ship channels are needed to assess changes from baseline data from increasing coastal development and vessel activities.